Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3344/kjp.2013.26.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Urinary Retention and Motor Weakness of Lower Extremities in a Postherpetic Neuralgia Patient

Abstract: During the early stage of postherpetic neuralgia, an epidural block on the affected segment is helpful in controlling pain and preventing progression to a chronic state. The main neurologic complication following an epidural block is cord compression symptom due to an epidural hematoma. When neurologic complications arise from an epidural block for the treatment of postherpetic neuralgia, it is important to determine whether the complications are due to the procedure or due to the herpes zoster itself. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Such complications may arise before skin lesions appear and are likely underdiagnosed because they are masked by overriding pain [ 455 , 456 ]; they may also occur some time after HZ onset [ 452 , 457 , 458 ]. Other presentations include gastrointestinal or bladder dysfunction [ 10 ], myelitis [ 450 , 459 461 ], and myositis [ 462 ]. VZV infection is implicated in the aetiology of Guillain-Barré syndrome [ 463 – 465 ].…”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…Such complications may arise before skin lesions appear and are likely underdiagnosed because they are masked by overriding pain [ 455 , 456 ]; they may also occur some time after HZ onset [ 452 , 457 , 458 ]. Other presentations include gastrointestinal or bladder dysfunction [ 10 ], myelitis [ 450 , 459 461 ], and myositis [ 462 ]. VZV infection is implicated in the aetiology of Guillain-Barré syndrome [ 463 – 465 ].…”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…The HZ-induced motor paresis is rare but can occur in 0.5% to 5% of patients [4]. It usually appears 2-3 weeks after the onset of the maculopapular rash [23]. It was reported that HZ-induced motor paresis typically lasts at least several months, which is associated with high rates of PHN [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its characteristic symptom is a painful erythematous maculopapular rash in the involved dermatome [1]. Involvement of motor neurons is rare but occurs, leading to segmental motor paresis [234]. Most patients with zoster motor weakness will recover within one year of the onset, but 20% of the patients permanently experience weakness [3].…”
mentioning
confidence: 99%
“…It is therefore important to rule out spinal cord compression caused by an epidural hematoma. [ 3 ] If decompression is performed within 24 h of the initial symptoms, nerve injury can be minimized. The volume of the hematoma may play an important role in neurologic recovery, but this can vary depending on the relative size of the individual's spinal canal.…”
mentioning
confidence: 99%